Analysis of The User Satisfaction of Gopay in Jakarta Area - Hanif Giri Shihab; Setyo Ferry Wibowo; Shandy Aditya (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study analyzes Gopay user satisfaction in DKI Jakarta area. Amidst Indonesia's booming digital economy and the shift to cashless transactions, Gopay's role as a leading e-wallet is crucial, making user satisfaction vital for business sustainability. Employing a quantitative descriptive approach, data was collected via surveys from 170 Gopay users in DKI Jakarta, primarily young adults (18-29) and students. Data were analyzed using descriptive and exploratory factor analysis with SPSS version 25. Descriptive analysis showed respondents hold a highly positive perception across all five satisfaction dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. Factor analysis extracted five key factors—Completeness, Accurate, Appearance, Easy to Understand, and Information Availability—collectively explaining 68.601% of the total variance. These factors significantly contribute to overall user satisfaction. The findings offer valuable insights for Gopay to enhance services and foster user loyalty by focusing on these critical aspects of application quality.